Immune microenvironment of tumor-draining lymph nodes: insights for immunotherapy - Wei, Jiahuan; Li, Daozhang; Long, Haixia; Han, Mei (Frontiers in Immunology, 2025)
Tumor-draining lymph nodes (TDLNs) play a crucial role in modulating tumor immune responses and influencing the efficacy of immunotherapy. However, our current understanding of the microenvironment within these lymph nodes remains limited. Tumors not only impair the anti-tumor activity of CD8+ T cells by creating an immunosuppressive microenvironment, but they also facilitate immune evasion and promote metastasis by altering the structure and function of TDLNs. Research has shown that tumor-specific memory CD8+ T cells (TTSM) within TDLNs are essential for the efficacy of immune checkpoint inhibitors, such as PD-1/PD-L1 blockers. Moreover, the abnormal structure of TDLNs, along with the presence of immunosuppressive cells—such as regulatory T cells (Tregs), regulatory B cells (Bregs), and immunosuppressive dendritic cells (DCs)—contributes to tumor-mediated immune evasion. Therefore, gaining a deeper understanding of the immune microenvironment within TDLNs is essential for improving the effectiveness of immunotherapies and developing novel therapeutic strategies. This review explores various TDLN-based therapeutic strategies, addressing the controversies surrounding lymph node dissection, the use of TDLNs as a source of tumor-infiltrating lymphocytes (TILs) for therapy, targeting immunosuppressive cells within TDLNs, and methods to reverse the structural abnormalities of TDLNs. These strategies offer valuable insights and potential directions for advancing tumor immunotherapy.